(untitled) (مجلة العلوم الشاملة, 2026)
In this study the removal of chromium (VI) from aqueous solutions by using modified Eggshells (Eg-Fe) was investigated. The effects of pH, concentration of Cr(VI), Eg-Fe dosage and contact time on the removal process were studied. The results demonstrate that the chromium concentration and pH of solutions are the predominant factors affecting the removal of Cr(VI), it was observed that the removal capacity significantly decreased at pH value more than 6.5. While the removal efficiency exhibit a decreased tend with increasing of Cr(VI) concentration, while Eg-Fe dosage and contact time were not significantly influential. The optimal removal conditions were achieved at: pH 6.0, contact time was 120 minutes, while the best dose of the Eg-Fe started from 1.0 g, whereas the removal efficiency reached 82%.